Experimental Investigation of a Hybrid Thermal Management System for an Electric Vehicle Battery Module - Coşkun, Turgay; Coşkun, Turgay; Çetkin, Erdal (Izmir Institute of Technology, 2022)
Environmental concerns and limited energy sources of the world are driving force in electric vehicle technology improvements. One of the main components of the electric vehicles is battery cell. Using batteries in electric vehicles brings up new concerns such as safety problems, limit of range and so on. The temperature of the battery cell increases during charging/discharging and operation. There is an optimal temperature range (15ºC ─ 35ºC) for battery cells to maximize efficiency and prevent safety issues. The high temperature values in the battery cells can be result with fire and explosion. In addition, the performance of the battery cells is highly affected by operating temperatures. Therefore, thermal management of the battery cells is a necessity to overcome safety issues and maximize the battery performance. The feasibility of microchannel heat sink for battery cooling is investigated numerically and it is decided to continue with conventional length scales because of the higher pressure drop values in micro scales. Thus, a hybrid cooling system, using air and liquid solely or simultaneously, is developed and is introduced to a battery module. The battery module created by connecting three lithium-ion pouch cells in serial. According to the results, air cooling gives the more homogeneous temperature distribution. The lowest temperature values are observed in hybrid cooling system and temperature difference between the cells are reduced by 30% when compared to the water-cooling system. The temperature profile in air cooling shows that any increase in the ambient temperature (23ºC) or discharge rate will undergo a temperature rise in battery cells and optimal temperature ranges will be exceeded in that case. A step function, in a sequence of various discharge rate, is introduced to the battery module to determine cooling capacity of the air system during operation. The result show that the temperature of the cells is kept below 30ºC. The hybrid cooling is enabled to select cooling systems for the battery module with respect to operating condition; hence, the efficiency of the system is increased.

Çevresel kaygılar ve sınırlı enerji kaynakları, elektrikli araçlardaki gelişmelerin temel kaynağıdır. Elektrikli araçların ana bileşenlerinden bir tanesi pil hücresidir. Elektrikli araçlarda pil kullanımı güvenlik sorunları, menzil sınırı vb. yeni endişeleri de beraberinde getirmektedir. Pil hücrelerinin sıcaklığı, şarj, deşarj ve kullanım esnasında artmaktadır. Verimliliği en üst düzeye çıkarmak ve güvenlik sorunlarını önlemek açısından pil hücreleri için belirlenmiş optimum çalışma sıcaklık aralığı (15ºC ─ 35ºC) vardır. Pil hücrelerindeki yüksek sıcaklık değerleri yangın ve patlama ile sonuçlanmaktadır. Ayrıca pil hücrelerinin performansı sıcaklık değerlerinden yüksek oranda etkilenmektedir. Bu durum, güvenlik sorunlarının üstesinden gelmek ve pil performansını en üst düzeye çıkarmak için bir termal yönetim sisteminin gerekliliğini göstermektedir. Pil soğutma için mikro kanallı soğutma sisteminin uygulanabilirliği sayısal olarak araştırılmış ve mikro ölçekteki yüksek basınç düşüşleri nedeniyle normal ölçekli soğutma sistemi ile devam edilmesine karar verilmiştir. Bu nedenle, hava ve sıvı soğutmanın ayrı ayrı veya bütünleşik olarak uygulanabildiği bir hibrit soğutma sistemi geliştirilmiş ve pil modülüne uygulanmıştır. Pil modülü, üç adet lityum-iyon kese hücresinin seri bağlanmasıyla oluşturulmuştur. Deneyler sırasında ortam sıcaklığı 23ºC’de tutulmuş ve pil hücreleri 3C hızında deşarj edilmiştir. Sonuçlara göre, hava soğutma daha homojen bir sıcaklık dağılımı vermektedir. En düşük sıcaklık değerleri hibrit soğutma sisteminde gözlenmiştir ve hücreler arası sıcaklık farkı su soğutmalı sisteme göre %30 oranında azalmaktadır. Hava soğutmadaki sıcaklık profili, ortam sıcaklığındaki veya deşarj hızındaki olası bir artışın sonucu olarak optimum sıcaklık değerlerinin dışında kalınacağını göstermektedir. Hava soğutma sisteminin elektrikli araç aktif iken kapasitesini belirlemek adına pil modülü bir dizin sıra ile (3C-1C) deşarj edilmiştir. Sonuçlara bakıldığında, ortam sıcaklığı 23ºC iken, hava soğutma ile pil hücrelerin sıcaklığının 30ºC'nin altında tutulduğu görülmektedir. Hibrit soğutma sayesinde pil modülü için aracın kullanım durumuna göre uygun soğutma sistemini seçebilmekteyiz; dolayısıyla sistemin verimliliğini artırmaktayız.
Elektrikli araç pil modülü için hibrit ısıl yönetim sisteminin deneysel olarak incelenmesi
Thesis (Doctoral)--Izmir Institute of Technology, Mechanical Engineering, Izmir, 2022
Includes bibliographical references (leaves. 83-100)
Text in English; Abstract: Turkish and English
Keywords: Heat transfer; Forced convection; Hybrid cooling; Battery module